Rehabilitation of the Upper Extremity after Stroke: A Case Series Evaluating REO Therapy and an Auditory Sensor Feedback for Trunk Control - G. Thielman; P. Bonsall (Stroke Research and Treatment)
Background and Purpose. Training in the virtual environment in post stroke rehab is being established as a new approach for neurorehabilitation, specifically, ReoTherapy (REO) a robot-assisted virtual training device. Trunk stabilization strapping has been part of the concept with this device, and literature is lacking to support this for long-term functional changes with individuals after stroke. The purpose of this case series was to measure the feasibility of auditory trunk sensor feedback during REO therapy, in moderate to severely impaired individuals after stroke. Case Description. Using an open label crossover comparison design, 3 chronic stroke subjects were trained for 12 sessions over six weeks on either the REO or the control condition of task related training (TRT); after a washout period of 4 weeks; the alternative therapy was given. Outcomes. With both interventions, clinically relevant improvements were found for measures of body function and structure, as well as for activity, for two participants. Providing auditory feedback during REO training for trunk control was found to be feasible. Discussion. The degree of changes evident varied per protocol and may be due to the appropriateness of the technique chosen, as well as based on patients impaired arm motor control.